ANALYTICAL ESTIMATION OF THE OPTIMAL PV PANEL TILT BASED ON A CLEAR-SKY IRRADIANCE MODEL - Golubovska Elena; Citkuseva Dimitrovska Biljana; Golubovski Roman (Journal of Energy Technology, 2025)
PV panel tilt and sun tracking are crucial aspects of PV conversion efficiency. We propose an analytical methodology for estimation of the optimal PV panel tilt based on calculation of the sun`s position and the application of a clear-sky solar irradiance model. Our methodology outputs three angles referencing a geolocation and the moment of interest: the incidence angle q, the sun altitude a and the sun azimuth z. The irradiance model estimates the solar irradiation at a geolocation that can be used for PV conversion estimation based on specified tilt β. The moment PV power is used for calculation of the daily energy production, and the optimal β is identified in the tilt range of 0° to 90°. Seasonal division of the year is performed, and optimal seasonal tilt is estimated based on the maximally produced seasonal energy, tested with every corresponding β. The methodology is tested on four typical seasonal models - 12 months, 4 three-month quarters, 2 half-year seasons and a single optimal annual fixed β The preliminary simulations produced promising results consistent with the practical engineering implementations.